Glomerular Expression of S100A8 in Lupus Nephritis: An Integrated Bioinformatics Analysis - Qijiao, Wei; Zhihan, Chen; Makota, Panashe; Qing, Yan; Fei, Gao; Zhihong, Wang; He, Lin (Frontiers in Immunology, 2022)
Introduction: Lupus nephritis (LN) is a major risk factor of morbidity and mortality. Glomerular injury is associated with different pathogeneses and clinical presentations in LN patients. However, the molecular mechanisms involved are not well understood. This study aimed to explore the molecular characteristics and mechanisms of this disease using bioinformatics analysis. Methods: To characterize glomeruli in LN, microarray datasets GSE113342 and GSE32591 were downloaded from the Gene Expression Omnibus database and analyzed to determine the differentially expressed genes (DEGs) between LN glomeruli and normal glomeruli. Functional enrichment analyses and protein-protein interaction network analyses were then performed. Module analysis was performed using the Search Tool for the Retrieval of Interacting Genes and Cytoscape softwares. Immunofluorescence staining was performed to identify the glomerular expression of S100A8 in various ISN/RPS class LN patients. The image of each glomerulus was acquired using a digital imaging system, and the green fluorescence intensity was quantified using Image-Pro Plus software. Results: A total of 13 DEGs, consisting of 12 downregulated genes and one upregulated gene (S100A8), were identified in the microarray datasets. The functions and pathways associated with the DEGs mainly include inflammatory response, innate immune response, neutrophil chemotaxis, leukocyte migration, cell adhesion, cell-cell signaling, and infection. We also found that monocytes and activated natural killer cells were upregulated in both GSE113342 and GSE32591. Glomerular S100A8 staining was significantly enhanced compared to that in the controls, especially in class IV. Conclusions: The DEGs identified in the present study help us understand the underlying molecular mechanisms of LN. Our results show that glomerular S100A8 expression varies in different pathological types; however, further research is required to confirm the role of S100A8 in LN.